ANALISIS FAKTOR EKONOMI YANG MEMPENGARUHI KRIMINALITAS DI JAWA TIMUR - Evi Yulia Purwanti; Eka Widyaningsih (Jurnal Ekonomi-Qu, 2019)
East Java's economic growth always increase, but undistributed of income still exist, so it causes inequality. People who can not to suffice their necessities in high competition will cause friction that leads to conflict and are encouraged to do criminal. This research is purpose to find out the relation which factors that influence crime rates in East Java. Dependent variable used is the level of crime while the independent variable used are GDP per capita, populationdensity, poverty, and unemployment. The type of data used is secondary data from the Central Statistics Agency (BPS). The method used in this study is panel data with fixed effect model. The results showed that the variable GDP per capita, population density, poverty, and unemployment significantly influenced the variable crime rate in East Java. So the factors thatinfluence the level of crime in East Java can be explained by economic variables.